Analisis Kepuasan Nasabah Memilih Byond By BSI Berdasarkan Kualitas Layanan dan Keamanan Pada PT Bank Syariah Indonesia Tbk KCP Palembang - Indyra Muthia Amanda; Markoni Badri; Claudya Nurcahaya (Jurnal Manajemen Bisnis Era Digital, 2025)
This study aims to analyze customer satisfaction with the Byond by BSI service at PT Bank Syariah Indonesia Tbk KCP Palembang KM 6, focusing on the influence of service quality and security. The research population consisted of 2,800 customers, with a sample of 97 respondents selected through purposive sampling. A quantitative approach was employed, using a structured questionnaire as the primary data collection instrument. The collected data were analyzed using multiple linear regression, accompanied by instrument testing, classical assumption testing, as well as t-test, F-test, and the coefficient of determination (R²). The findings reveal that both service quality and security have a significant impact on customer satisfaction, both partially and simultaneously. The results indicate that customer satisfaction is not only determined by responsive, accurate, and accessible service quality but is also strongly influenced by the reliability of the security system provided. The regression coefficient shows that security has the most dominant effect, with a value of 0.427, which is higher than the influence of service quality. This highlights that the sense of safety in conducting digital transactions is the primary concern for customers when using Byond by BSI services. The implications of this study emphasize the importance for banks to continuously improve the quality of digital services, particularly in terms of responsiveness, speed of access, and ease of use of the application. In addition, strengthening digital security mechanisms, including customer data protection, transaction encryption, and early detection of potential cyber threats, is crucial in building and maintaining customer trust. The study further underlines the need for continuous improvement in both service quality and security systems as a key strategy to address the challenges of digital banking transformation in an increasingly competitive environment. Therefore, this research contributes to the development of Islamic banking management strategies that focus on customer satisfaction and loyalty in the digital era.